Growth and solar energy conversion in common bean grown under three nitrogen levels and two water systems - Costa, Roberto C. L.; Lopes, Nei F.; Oliva, Marco A.; Barros, Nairan F. (Pesquisa Agropecuaria Brasileira, 2014)
Growth and solar energy conversion in common bean (Phaseolus vulgaris L.) cv. Negrito 897 grown under three nitrogen levels (50, 125 and 200 ppm of N) ad two water systems (field capacity and cyclic water stress from -0.03 to - 1.0 MPa) were studied in the greenhouse; The water system showed greater effect on growth than nitrogen levels, though high nitrogen level minimized the hydric stress effects, producing plant hardening by increment in the root development. The water deficit reduced and high nitrogen level increased the efficiency of solar energy conversion.